ANALISIS YURIDIS PENYELESAIAN SENGKETA PEMBAGIAN HARTA BERSAMA/GONO-GINI UNTUK MEWUJUDKAN KEPASTIAN HUKUM (STUDI PENELITIAN PADA KANTOR PENGADILAN AGAMA BATAM) - Rahman Wahid Rambe; Laily Washliati; Lia Fadjriani (Ensiklopedia of Journal, 2022)
Basically every implementation of a divorce will certainly cause a legal consequence between every couple who ends their marital relationship, one of the legal consequences is regarding the joint property produced in their marriage. So this becomes a very important urgency if a marriage ends in a divorce. Cases related to divorce and disputes regarding the distribution of joint property for those who are Muslims occur throughout the Batam City area where the dispute is resolved in the Religious Courts that are adjusted to their authority. The research problem is, How is the Dispute Settlement of the Distribution of Joint Assets / Gono-gini in the Batam Religious Court. This study uses a descriptive method by using a normative approach (Legal Research) to obtain secondary data and an empirical approach (Sociological Juridical) to obtain primary data and through a field approach (Field Research). In Islamic law, joint property is also known as syirkah. Syirkah is a mixture, in this case, it is a mixture of assets obtained by husband and wife during the marriage. Assets that are united due to syirkah during marriage become joint property. In the event of a divorce, the syirkah assets are divided between husband and wife according to the consideration of the extent of their efforts in obtaining the property. Article 97 of the Compilation of Islamic Law states that divorced widows or widowers are each entitled to one-half of the joint property as long as it is not specified otherwise in the marriage agreement. In the decision number 1438/Pdt.G/2020/PA.Btm. The Panel of Judges has decided that the distribution deviates from the applicable provisions with a percentage for the husband . and wife for the joint property. The results of this study are that the basic considerations used by the Panel of Judges in making this decision have been thinking more forward on progressive legal values, so that in deciding this case the Panel of Judges has overridden the applicable provisions and according to the view of Islamic law that these considerations are in accordance with justice. in Islam, namely based on balance, equality and non-discrimination, granting rights to the entitled and the delegation of existence based on the level of eligibility.    Keywords: Settlement, Dispute, Sharing of Shared Assets, Gono-gini, Legal Certainty